2022
DOI: 10.3390/ijms23168851
|View full text |Cite
|
Sign up to set email alerts
|

Bromocriptine-QR Therapy Reduces Sympathetic Tone and Ameliorates a Pro-Oxidative/Pro-Inflammatory Phenotype in Peripheral Blood Mononuclear Cells and Plasma of Type 2 Diabetes Subjects

Abstract: Bromocriptine-QR is a sympatholytic dopamine D2 agonist for the treatment of type 2 diabetes that has demonstrated rapid (within 1 year) substantial reductions in adverse cardiovascular events in this population by as yet incompletely delineated mechanisms. However, a chronic state of elevated sympathetic nervous system activity and central hypodopaminergic function has been demonstrated to potentiate an immune system pro-oxidative/pro-inflammatory condition and this immune phenotype is known to contribute sig… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

0
24
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(24 citation statements)
references
References 253 publications
0
24
0
Order By: Relevance
“…[ 36 ] The precise mechanisms underlying the antidiabetic effects of bromocriptine remain unclear. In addition, bromocriptine treatment shows reduced low‐grade systemic inflammation in clinical trials or preclinical studies, [ 37 , 38 ] but the underlying mechanisms are largely unknown. Our findings support CREBZF acts as a new mechanism of bromocriptine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…[ 36 ] The precise mechanisms underlying the antidiabetic effects of bromocriptine remain unclear. In addition, bromocriptine treatment shows reduced low‐grade systemic inflammation in clinical trials or preclinical studies, [ 37 , 38 ] but the underlying mechanisms are largely unknown. Our findings support CREBZF acts as a new mechanism of bromocriptine treatment.…”
Section: Discussionmentioning
confidence: 99%
“…Francesco et al demonstrated that Pin1 exacerbates hyperglycemia-induced reactive oxygen species (ROS) production and mitochondrial oxidative stress in human aortic endothelial cells (HAECs) through the translocation of p66Shc, a prooxidant adaptor ( Pinton et al, 2007 ; Paneni et al, 2015 ). Suppression of Pin1, through gene silencing, Juglone treatment, Vitamin D receptor (VDR) agonists, or bromocriptine-QR, alleviates chronic oxidative stress and vascular dysfunction induced by diabetes ( Paneni et al, 2015 ; Costantino et al, 2016 ; Zhang et al, 2018 ; Cincotta et al, 2022 ). Similar effects of Pin1 on p66Shc translocation and ROS accumulation were observed in intestinal ischemia/reperfusion (I/R) injury and hippocampal neuronal oxidative stress ( Zhu et al, 2014 ; Feng et al, 2017 ).…”
Section: Representative Pathophysiological Roles Of Pin1mentioning
confidence: 99%
“…A bromocriptine quick-release formulation was designed as a glucose-lowering drug and approved for clinical use by the FDA in 2009 (commercialized as CYCLOSET ® ). Recent evidence indicates that circadian-timed bromocriptine quick-release treatment reduces the sympathetic tone and improves systemic low-grade inflammation in type 2 diabetes subjects ( 108 ). Thus, these findings help to explain how circadian-timed DA administration is able to improve the metabolic status of patients and reduce the risk of cardiovascular diseases, independently of their effects on prolactin secretion.…”
Section: Insulin Resistance and Hyperglycemiamentioning
confidence: 99%